Isolated retroperitoneal mixed germ cell tumor presenting as acute abdomen – case report - Misiak, Piotr; Piskorz, Łukasz; Jabłoński, Sławomir; Mikosiński, Jacek; Brocki, Marian; Wcisło, Szymon (Contemporary Oncology/Współczesna Onkologia, 2013)
Extragonadal germ cell tumors are an uncommon clinical entity. Their prevalence varies between 1 and 5% of all germ cell tumors. Approximately 85–90% of cases have metastatic changes at the time of diagnosis. In our article we would like to present a case of an 18-year-old patient who was admitted to the hospital due to acute abdominal symptoms. A day earlier, the patient suffered blunt abdominal trauma during workout. Post-traumatic changes, which were described after admission in computed tomography, intraoperatively proved to be masses of extraperitoneal tumor.